Review: Associations among goods, impacts and ecosystem services provided by livestock farming - B. Dumont; J. Ryschawy; M. Duru; M. Benoit; V. Chatellier; L. Delaby; C. Donnars; P. Dupraz; S. Lemauviel-Lavenant; B. Méda; D. Vollet; R. Sabatier (Animal, 2019)
Livestock is a major driver in most rural landscapes and economics, but it also polarises debate over its environmental impacts, animal welfare and human health. Conversely, the various services that livestock farming systems provide to society are often overlooked and have rarely been quantified. The aim of analysing bundles of services is to chart the coexistence and interactions between the various services and impacts provided by livestock farming, and to identify sets of ecosystem services (ES) that appear together repeatedly across sites and through time. We review three types of approaches that analyse associations among impacts and services from local to global scales: (i) detecting ES associations at system or landscape scale, (ii) identifying and mapping bundles of ES and impacts and (iii) exploring potential drivers using prospective scenarios. At a local scale, farming practices interact with landscape heterogeneity in a multi-scale process to shape grassland biodiversity and ES. Production and various ES provided by grasslands to farmers, such as soil fertility, biological regulations and erosion control, benefit to some extent from the functional diversity of grassland species, and length of pasture phase in the crop rotation. Mapping ES from the landscape up to the EU-wide scale reveals a frequent trade-off between livestock production on one side and regulating and cultural services on the other. Maps allow the identification of target areas with higher ecological value or greater sensitivity to risks. Using two key factors (livestock density and the proportion of permanent grassland within utilised agricultural area), we identified six types of European livestock production areas characterised by contrasted bundles of services and impacts. Livestock management also appeared to be a key driver of bundles of services in prospective scenarios. These scenarios simulate a breakaway from current production, legislation (e.g. the use of food waste to fatten pigs) and consumption trends (e.g. halving animal protein consumption across Europe). Overall, strategies that combine a reduction of inputs, of the use of crops from arable land to feed livestock, of food waste and of meat consumption deliver a more sustainable food future. Livestock as part of this sustainable future requires further enhancement, quantification and communication of the services provided by livestock farming to society, which calls for the following: (i) a better targeting of public support, (ii) more precise quantification of bundles of services and (iii) better information to consumers and assessment of their willingness to pay for these services.